Connotations of the comedic text between the internal and external levels in the cinematic film... The Modern Times film as an example (Al-Academy, 2024)
The main function of film discourse is its ability to present ideas, connotations, and meanings and deliver them to the recipient, and because the comedy text is one of those film discourses that communicates its philosophical ideas by presenting them through comedy, and through the comic situation and arousing laughter in the viewer, which works according to two levels, one of which is what the viewer sees at The screen and the other are absent" between the lines. The viewer senses it through codes that reach him. This research is an attempt to know and reveal the types of codes that work to activate the comedic text. The researcher has chosen one of Charlie Chaplin's films, the movie Modern Times, to study the nature of the formation of codes in order to form references. Simple knowledge that contributes to moving the comic text forward.